Deficiencies in Bureaucracy and Communication Hindering Youth Posyandu Implementation in Pasuruan: Kekurangan dalam Birokrasi dan Komunikasi Menghambat Pelaksanaan Posyandu Pemuda di Pasuruan - Wiyanto, Chyntia Febrianti; Choiyirah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background The importance of youth as the nation's successor is underscored by national health issues, notably the alarming rise in premarital sexual activity, necessitating robust public health programs. Specific Background In response to Ministry of Health Regulation No. 25/2014, the Youth Posyandu Program was initiated in Pasuruan City as a community-based effort to address adolescent health. Knowledge Gap Despite strong policy support, the actual success of this program at the village level (Kelurahan Petahunan) remains unevaluated against implementation theory. Aims This qualitative descriptive study aims to determine the implementation status of the Youth Posyandu Program in Petahunan Village based on Edward III's model (communication, resources, disposition, and bureaucratic structure). Results Findings indicate that the implementation remains unsatisfactory across all four variables. Key shortcomings include deficiencies in communication delivery and, crucially, the absence of a formal Standard Operating Procedure (SOP) within the bureaucratic structure. Novelty This study provides a specific field assessment of a vital public health program using a proven policy implementation model, revealing structural and communicational weaknesses at the sub-district level. Implications Local policymakers must prioritize the development of formal SOPs and improve communication strategies for sustainable program execution. Highlights: Implementation of the Youth Posyandu Program in Petahunan is unsatisfactory based on four key variables. Deficiencies were found in communication delivery to the target youth audience. The absence of a formal SOP is a major structural impediment to program consistency. Keywords: Policy Implementation, Youth Posyandu, Edward III Model, Communication, Bureaucratic Structure